Consequences of shortened hunting seasons by the Birds Directive on late winter teal Anas crecca abundance in France. Issue 3 (27th July 2021) - Guillemain, Matthieu; Vallecillo, David; Grzegorczyk, Emilienne; Mouronval, Jean-Baptiste; Gauthier-Clerc, Michel; Tamisier, Alain; Champagnon, Jocelyn
Abstract : The European Birds Directive (EBD) prevents hunting during spring migration, primarily to facilitate birds' use of habitats before and during the prenuptial journey. In line with the EBD requirements, the hunting season for waterfowl in southern France was shortened by two months during February–March since the mid‐1950s. However, consequences of such hunting bans for late winter habitat use have not been evaluated. We investigated a 55‐years dataset from a major international wintering ground to assess whether the EBD‐related changes in hunting legislation have led to increased regional teal Anas crecca numbers during late winter. Teal abundance in the Camargue during late winter increased over the last decades: the ban on hunting in February was the best predictor of teal numbers during that month, leading to a sudden 50% increase in relative abundance. In March a more gradual temporal increase since the mid‐1960 was instead recorded. Whether the increase in teal during late winter resulted from locally wintering birds or those from elsewhere stopping in the Camargue cannot be discerned. Nonetheless, the increase in teal numbers supports the basis for the EBD, in that a ban on hunting during late winter is associated with a greater use of habitats during this crucial part of the annual cycle, especially in February.